Entropy inequalities for semigroup actions. (6th June 2022) - Carvalho, Maria; Rodrigues, Fagner B; Varandas, Paulo
Abstract: We extend Margulis–Ruelle inequality to the general setting of semigroup actions which are finitely generated either by Lipschitz continuous maps acting on a compact metric space or by smooth maps on a compact Riemannian manifold. We also discuss a few examples to illustrate the sharpness of our estimates.